Success factors for initial works of industralised building system process of projects implementation / Faridah Ismail, Norazian Mohamad Yusuwan and Har Einur Azrin Baharuddin. - Ismail, Faridah Hanim; Mohamad Yusuwan, Norazian; Baharuddin, Har Einur Azrin (Universiti Teknologi MARA Cawangan Selangor, 2018)
The absence of success factors focusing on the Industrialised Building System (IBS) process of project implementation initiates this study. Therefore, the aim of this research is to establish the success factors within the initial works of the IBS process of project implementation. Comprehensive literature review revealed that success factors are; the management, the government policies and initiatives, the coordination between design and construction, and the technical aspects of project deliverables. Questionnaire survey distributed amongst G7, IBS contractors unanimously agreed on these as success factors for the initial works of the IBS process of project implementation.